IMPLEMENTATION OF E-GOVERNMENT AS A PUBLIC SERVICE IN WARINGINSARI TIMUR VILLAGE - Lailatul Istikomah; Rinawati Rinawati; Desi Handayani (IJISCS (International Journal of Information System and Computer Science), 2018)
Based on the results of the Indonesian e-government rating (PeGI) at the provincial level at the end of 2015, Lampung province received the title of 17 out of 20 under the category of less. E-government for government institutions is useful to improve the quality of public services in providing information to the public, improving relations between government, community empowerment and implementing a more efficient government. Waringinsari Timur Village is a village that needs to be answered by government agencies in carrying out its functions, namely improving the quality of public services and a wealth of potential villages that are income-generating such as livestock, plantations, agriculture, small industries / homes. Researchers conducted a study by building a website application with the theme "Implementation of E-Government as a Public Service in East Waringinsari Village".System development is carried out based on the System Development Life Cycle (SDLC) method approach which includes the stages of system planning, analysis, design and implementation. Data collection methods are carried out by means of observation, interviews, and literature studies. Of the 30 respondents who answered the questionnaire and conducted a website test that was made, 73.3% of the respondents answered "YES" and were satisfied with the website of East Waringinsari village. While 26.7% answered "NO" and were not satisfied with the website of East Waringinsari village. With a website in Waringinsari Timur village, it will be easier to search information quickly, precisely, accurately, and without limits because it can be accessed anywhere and anytime.